2004
DOI: 10.1002/jms.587
|View full text |Cite
|
Sign up to set email alerts
|

A Top‐down method for the determination of residue‐specific solvent accessibility in proteins

Abstract: We present a method employing top-down Fourier transform mass spectrometry (FTMS) for the rapid profiling of amino acid side-chain reactivity. The reactivity of side-chain groups can be used to infer residue-specific solvent accessibility and can also be used in the same way as H/D exchange reactions to probe protein structure and interactions. We probed the reactivity of the N-terminal and epsilon-lysine amino groups of ubiquitin by reaction with N-hydroxysuccinimidyl acetate (NHSAc), which specifically acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
79
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 27 publications
6
79
0
Order By: Relevance
“…Previous studies have shown that reactivity is influenced mainly by the solvent accessibility of the amino acid and of the reactive atom. 23,25,29,30 The rate coefficients in Tables 1 and 2 indicate that there is not a simple correlation between the modification rates and the solvent accessibility of the entire side chain. The % SASA ratio does not seem to always correlate with the reaction rates.…”
Section: Factors Affecting the Reactivity Of Functional Groupsmentioning
confidence: 99%
“…Previous studies have shown that reactivity is influenced mainly by the solvent accessibility of the amino acid and of the reactive atom. 23,25,29,30 The rate coefficients in Tables 1 and 2 indicate that there is not a simple correlation between the modification rates and the solvent accessibility of the entire side chain. The % SASA ratio does not seem to always correlate with the reaction rates.…”
Section: Factors Affecting the Reactivity Of Functional Groupsmentioning
confidence: 99%
“…This instrument was described in detail in a previous publication [11]. After labeling or cross-linking and purification, protein samples were diluted to 10 M in 50:50 MeOH:H 2 O with 6% acetic acid and were introduced via direct infusion to an Apollo ESI ion source (Bruker Daltonics, Billerica, MA) at a flow rate of 1.5 L/min.…”
Section: Sample Analysismentioning
confidence: 99%
“…Examination of the known structure of ubiquitin showed that there are many geometrically allowed cross-links be-tween primary amino groups that were not observed experimentally. To determine whether our method could not localize these cross-links or if the cross-links were not formed, we probed the reactivity of the primary amino groups of ubiquitin by reaction with N-hydroxysuccinimidyl acetate (NHSAc), which specifically acetylates primary amines by the elimination of N-hydroxy succinimide; this is the same elimination reaction that occurs twice in the cross-linking reaction with the disuccinimidyl esters [11]. As the stoichiometric ratio of NHSAc:protein increased, identification of the fragments from native protein and protein with successively increasing modification allowed the assignment of the complete order of reactivity of the primary amino groups in ubiquitin (Met1 Ϸ Lys 6 Ϸ Lys 48 Ϸ Lys 63 Ͼ Lys 33 Ͼ Lys11 Ͼ Lys 27, Lys 29).…”
mentioning
confidence: 99%
“…Acetic anhydride was the earliest lysine derivatization reagent used [18]. More recently, however, lysine targeted labeling strategies have shifted towards the use of N-hydroxysuccinimide (NHS) esters, due to their improved reaction specificity and a roughly 1000-fold lower required concentration compared with acetic anhydride [22][23][24][25][26]. Lysine-specific modification by S-methylthioacetimidate has also been recently reported [27].…”
mentioning
confidence: 99%